Analisis Kesulitan Belajar Peserta Didik pada Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti di Kelas XI Fase F SMA N 3 Lubuk Basung Kabupaten Agam - Ardiningrum, Ailsya Regita; Rivauzi, Ahmad (Lembaga Yasin AlSys, 2025)
The phenomenon of learning difficulties in Islamic Religious Education (IRE) subjects remains under-researched, despite its significant impact on students’ academic achievement. This study aims to identify the types of learning difficulties encountered, analyze their causal factors, and examine the IRE learning process in Grade XI Phase F at SMAN 3 Lubuk Basung. A qualitative case study approach was employed, involving 28 purposively selected students. Data were collected through interviews, observations, and documentation, and analyzed thematically. The findings reveal that students primarily struggle with memorizing ayat and understanding content that requires critical thinking skills. Contributing factors include low learning motivation, lack of parental support, and limited learning facilities. These findings reinforce the relevance of constructivist theory, which emphasizes the need to align teaching methods with students’ characteristics. The study concludes that adaptive learning strategies and a supportive learning environment are essential. Its implications contribute to theoretical discourse and offer practical recommendations for schools and educators to enhance the quality of IRE instruction, while also paving the way for future research on technology-based interventions or targeted support programs for students experiencing learning difficulties.